Cloud computing and electronic discovery - Martin, James P.; Cendrowski, Harry (Hoboken, New Jersey : John Wiley and Sons, 2014)
This book prepares fraud investigators, legal professionals, forensic accountants and executives with understanding the ramifications of storing data with third party providers and how such storage mechanisms relate to the limits of discovery practices. It has a discussion of the few existing legal precedents and current cases that are shaping interpretation of discovery laws in the cloud space. Topics include: an overview of current trends in cloud computing; litigation that involves data held by a cloud service provider; updates on laws governing discovery of information held by a third party cloud service provider; updates on legal cases that address the issues of the Electronic Communication Privacy Act; practical guidance on how to consider the availability of cloud data relevant to an investigation, and how to include this data in discovery plans. --
Cloud computing definitions and technical considerations / Christopher Thieda -- The proliferation of data available for discovery / James P. Martin and Harry Cendrowski -- Cloud migration and planning for retention / James P. Martin and Harry Cendrowski -- Brief history of privacy and selected electronic surveillance laws / James P. Martin and Harry Cendrowski -- Electronic Communications Privacy Act / James P. Martin and Harry Cendrowski -- Proposed legislative changes and future laws / James P. Martin and Harry Cendrowski -- The control concept and related issues / Matthew breuer and harry cendrowski -- Current issues in Cloud data / James P. Martin and Harry Cendrowski -- The rise of social media and its role in litigation / Sarah Marmour and Dierdre Fox -- Cloud computing and reasonable expectations of privacy : Fourth Amendment concerns / Matthew Breuer and Harry Cendrowski -- Modern case analysis shaping litigation / Matthew Breuer and Harry Cendrowski -- Compelled production of Cloud computing data : Fifth Amendment concerns / Matthew Breuer and Harry Cendrowski.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
English.
John Wiley and Sons
Keywords: United States; Electronic Communications Privacy Act of 1986 (United States); Cloud computing -- Law and legislation -- United States; Electronic discovery (Law) -- United States; Privacy, Right of -- United States; z; LAW -- Civil Procedure; LAW -- Legal Services; POLITICAL SCIENCE -- Government -- Judicial Branch; Cloud computing -- Law and legislation; Electronic discovery (Law); Privacy, Right of; United States